Women' exploitation patterns as narcotics couriers: A study of participating victim - Lestari, Gayatri Ayu; Margaret, Monica (Jurnal Anifa: Studi Gender dan Anak, 2024)
This research discusses the pattern of exploitation of women by their partners as drug couriers. This research uses the study of participating victims, namely someone who unconsciously becomes a victim because of his attitude that encourages him to become a victim. The purpose of this study is to analyze the recruitment patterns used by men as crime planners involving women as drug couriers. Thus, the pattern of exploitation that has occurred is expected to be the primary step in limiting drug couriers who use women as intermediaries in their crimes. Over five months, this study was carried out at the Pondok Bambu, Jakarta, and Tangerang Class II A Women's Correctional Institution. The subjects of this research were four informants involved in the crime and one informant from the Community Legal Aid Institute in Jakarta, who handled the case. This research uses a descriptive-qualitative approach with primary data sources and secondary data, namely, the results of interviews with research subjects and informants related to this crime, then examined in the form of narrative descriptions and using secondary data such as news, books, and data related to the research. The study's findings indicate that women become involved in drug-related crimes when they meet their partners, and then the partners use these women's emotions as leverage to conduct the crimes. In addition, the factor of being a victim of violence is also very influential on the existence of women involved in drug crime cases. Women's involvement in this case shields the male spouse from legal obligations and is not defended based on the pattern of exploitation they get, but women are convicted based on the evidence found against them.